2002
DOI: 10.1007/s00572-002-0172-y
|View full text |Cite
|
Sign up to set email alerts
|

The arbuscular mycorrhizal fungus Glomus geosporum in European saline, sodic and gypsum soils

Abstract: Plants of saline and sodic soils of the Hungarian steppe and of gypsum rock in the German Harz mountains, thus soils of high ionic strength and electric conductivity, were examined for their colonization by arbuscular mycorrhizal fungi (AMF). Roots of several plants of the saline and sodic soils such as Artemisia maritima, Aster tripolium or Plantago maritima are strongly colonized and show typical AMF structures (arbuscules, vesicles) whereas others like the members of the Chenopodiaceae, Salicornia europaea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 40 publications
(63 reference statements)
7
87
1
5
Order By: Relevance
“…characters of fruiting structures and spores. Moreover, the result was reinforced by comparing the entire ITS (ITS1-5.8s-ITS2) rDNA sequences with the available data of GenBank databases through the NCBI BLAST search algorithm (Altschul et al, 1997;Liang and Gao, 2000;Girlanda et al, 2002;Landwehr et al, 2002;Bougoure and John, 2005). Due to the large number of isolates and complications of identifi cation of the endophytic fungi, 5 strains were identifi ed at the genus or species level, whereas 6 unidentifi ed strains belonging to ascomycetes are still unnamed.…”
Section: Resultsmentioning
confidence: 99%
“…characters of fruiting structures and spores. Moreover, the result was reinforced by comparing the entire ITS (ITS1-5.8s-ITS2) rDNA sequences with the available data of GenBank databases through the NCBI BLAST search algorithm (Altschul et al, 1997;Liang and Gao, 2000;Girlanda et al, 2002;Landwehr et al, 2002;Bougoure and John, 2005). Due to the large number of isolates and complications of identifi cation of the endophytic fungi, 5 strains were identifi ed at the genus or species level, whereas 6 unidentifi ed strains belonging to ascomycetes are still unnamed.…”
Section: Resultsmentioning
confidence: 99%
“…Most halophyte species are non-mycorrhizal. Molecular biological techniques revealed that 80%, on average, of the AM spores isolated from a range of European saline soils belonged to one single species, Glomus geosporum, which occurred much less in the surrounding non-saline habitats (Hildebrand et al, 2001;Landwehr et al, 2002). The authors speculate that specific AM ecotypes may be particularly adapted to saline conditions and that they could have a great potential in conferring salt tolerance to plants.…”
Section: Effect Of Salinity On Am Colonization and Spore Numbermentioning
confidence: 95%
“…Interestingly, the most commonly observed AM fungus was among Glomus spp. (Landwehr et al, 2002). However, when comparing several Glomus spp., Porras-Soriano et al (2009) observed that each AM fungal species has a different efficiency in alleviating plant salt stress.…”
Section: Mycorrhiza and Alleviation Of Plant Salt Stressmentioning
confidence: 99%
“…Another factor that has to be taken into account in such habitats is drought, which can be more important than salt for the abundance of AM fungi in halophytes (Füzy et al 2008). Attempts to identify the AM fungal species associated with plants in saline habitats revealed that at least in Europe, most isolates belong to the Glomus geosporum/Glomus caledonium cluster (Hildebrandt et al 2001;Landwehr et al 2002;Sonjak et al 2009). In addition to arbuscular mycorrhiza, some papers report the occurrence of so-called dark septate endophytes (DSEs).…”
Section: Interaction Of Micro-organisms With Host Plantsmentioning
confidence: 99%